Assessment of organizational culture types, leadership styles and their relationships within governmental and non-governmental hospitals in Gaza Strip of Palestine - Hatem H. Alsaqqa; Çağdaş E. Akyürek (BMC, 2021)
Abstract Background The subjects of organizational culture and leadership have been studied several times in various fields. However, studies have tried to determine the relationship between corporate culture and leadership as it is still indistinguishable, or more evidence is needed. The paper describes the perceptions of the staffs about the hospitals' organizational culture types and their managers' leadership styles in these hospitals and the relationships that may exist between these domains. Method This is a cross-sectional descriptive study involving 400 participants from three governmental and two non-governmental hospitals during the period from June to December 2018. The target population included all categories of staff working at hospitals as physicians, nurses, paramedics and administrators. Results The largest number of participants was 82.5 % from government hospitals while 17.5 % were from non-governmental hospitals. Clan and hierarchy-driven cultures were the top-defined forms of organizational culture at hospitals in the Gaza Strip. In all types of organizational culture, the non-governmental hospitals which all are small size hospitals have higher perceptions' means than the governmental ones that have different sizes. Managers' styles in the investigated hospitals were transformational and transactional. The study's results showed significant positive associations by Pearson's Correlations and effect by linear multiple regression analysis between styles of transformation and transactional leaderships and types of organizational cultures. Discussion and conclusion The study addressing the main concepts showed positive relations and also impacts between two of the leadership styles and organizational culture types, apart from the Laissez-faire style. This paper has been successful in contributing to the research on this topic and providing indications for understanding certain domains of the hospital industry in Palestine.